2015
DOI: 10.1089/acu.2014.1079
|View full text |Cite
|
Sign up to set email alerts
|

Third Stage of Labor and Acupuncture

Abstract: Acupuncture use in obstetrics has been increasing in Western medicine, especially to alleviate complications of pregnancy, the most important cause of maternal mortality worldwide. One quarter of maternal deaths are caused by complications in the third stage of labor, an interval between complete delivery of the baby and the complete expulsion of the placenta. This review analyzes the increased acupuncture use for pregnancy complications as a potential method of reducting maternal mortality during the third st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Even third stage itself has been widely discussed recently, especially in relationship to postpartum hemorrhage. Some studies suggest that acupuncture may be a method to avoid or treat retained placentae (Djakovic et al., ). And based on observations that animal consume their own placentae, some women are consuming capsules of their dried placentae to promote maternal health and lactation, although a review suggests little has been reported on either benefits or risks of this phenomenon (Coyle et al., ).…”
mentioning
confidence: 99%
“…Even third stage itself has been widely discussed recently, especially in relationship to postpartum hemorrhage. Some studies suggest that acupuncture may be a method to avoid or treat retained placentae (Djakovic et al., ). And based on observations that animal consume their own placentae, some women are consuming capsules of their dried placentae to promote maternal health and lactation, although a review suggests little has been reported on either benefits or risks of this phenomenon (Coyle et al., ).…”
mentioning
confidence: 99%